UNTRANSLATED INDONESIAN WORDS IN THE TRANSLATION OF EKA KURNIAWANâ€™S NOVEL â€œBEAUTY IS A WOUNDâ€ - Rachelina Larasati; Ouda Teda Ena (PROJECT (Professional Journal of English Education), 2023)
This research was aÂ  descriptive qualitative study that aimed to investigate the untranslated Indonesian words found in the English translation of â€œCantik itu Lukaâ€ novel, which is â€œBeauty is A Woundâ€. The analysis was done using comparative method to find out how the translator convey the meaning of the untranslated words intended by the author to the readers of the target language. In this study, it was found that cultural-bound words referring to ecology; material culture such as food and drink; social culture, custom and religious activities; and gestures and habits were left untranslated. The finding showed that in conveying the meaning, the translator used amplification and transposition translation techniques... It was also found that some words were left untranslated without further descriptions which caused meaning to be untransferred.Â Keywords:Â  Translation; Novel; Cultural Words